Kompetensi Pedagogik Guru Pendidikan Agama Islam dalam Pencegahan Perilaku seks Menyimpang Siswa - Siti Nurwinda; M.Fadlani Salam; Supala (UIN Sunan Gunung Djati Bandung, 2022)
A very important component in education is related to teachers and students, so that educational goals are achieved, it requires teachers who have competence. Especially pedagogic competence, pedagogic competence is very important for a teacher who will manage learning optimally, and can educate students well so that students can increase knowledge about the dangers of deviant sexual behavior in themselves and others. The purpose of this study was to determine the quality of the pedagogic competence of PAI teachers, to determine sex education and to determine the factors supporting and inhibiting the pedagogic competence of PAI teachers in preventing students' deviant sexual behavior. In this study using a qualitative approach by using a descriptive research model. The results of the study concluded that 1) The pedagogic competence of PAI teachers was quite good starting from the ability to manage learning, understanding students, implementing learning for students, educating students, and evaluating learning outcomes, this can be seen from the learning activities in the teacher's classroom make RPP before delivering materials and teaching materials. 2) Sex education still needs to be improved in understanding knowledge, educating participants and maximizing the competence of PAI teachers, 3) Supporting factors and inhibiting pedagogical competencies of PAI teachers in preventing deviant sexual behavior in students is the support from teachers who are very large to provide knowledge about sex so that teachers work together to remind this education to students. The inhibiting factor in the pedagogic competence of PAI teachers in preventing deviant sexual behavior is the lack of facilities and infrastructure in schools that support providing knowledge about sex education and deviant behavior, as well as the home environment and friendship environment which are inhibiting factors for sex education.